2020
DOI: 10.3389/fonc.2020.00365
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of American Joint Committee on Cancer Staging for Stage III Renal Cell Carcinoma With Nodal Involvement: Propensity Score Matched Analyses of a Large Population-Based Study

Abstract: Background: To assess the role of nodal involvement in stage III renal cell carcinoma (RCC) according to the American Joint Committee on Cancer (AJCC) 8th staging system. We compared the survival outcomes of RCC patients with pT 1−3 N 1 M 0 disease and those with pT 3 N 0 M 0 or stage IV (stratified as pT 4 N any M 0 and pT any N any M 1) disease in a large population-based cohort. Methods: A cohort of 3,112 eligible patients with RCC was identified from the Surveillance, Epidemiology, and End Results (SEER) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Furthermore, LND provides important staging, prognostic, and counseling value, which based on recent studies has drastic survival outcomes. 3,29,30 The onus of creating a more accurate TNM staging system will need to be a multidisciplinary effort in order to provide physicians with reliable information for counseling patients and accurately stratifying patients within clinical trials and standard of care practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, LND provides important staging, prognostic, and counseling value, which based on recent studies has drastic survival outcomes. 3,29,30 The onus of creating a more accurate TNM staging system will need to be a multidisciplinary effort in order to provide physicians with reliable information for counseling patients and accurately stratifying patients within clinical trials and standard of care practice.…”
Section: Discussionmentioning
confidence: 99%
“…Like Yu et al, our data shows that Stage III node-positive disease (22.7%; 95% CI: 20.6%-24.9%) and Stage IV RCC patients and (15.6%; 95% CI: 11.1%-23.8%) have similar 5-year survival rates. Recently, Han et al used the Surveillance, Epidemiology, and End Results (SEER)database performed a similar analysis to compare survival outcomes for patients with pT1-3N1M0 to pT3N0M0 and pT1-3N0M1 RCC 30. Using propensity score matching to adjust for baseline confounders, patients with Stage III nodal-positive had similar OS and cancer-specific survival (CSS) to patients with Stage IV disease (median OS 41.0 vs. 38.0 months, p=0.77; CSS 45.0 vs. 39.0 months, p=0.59).…”
mentioning
confidence: 99%
“…Srivastava et al analyzed 8988 patients with RCC who underwent RN and retroperitoneal LND and showed that pN1 stage III disease was inferior to pN0 stage III and was similar to stage IV disease with respect to OS [41]. Similarly, several studies have also shown that stage III disease patients had similar survival estimates, such as OS and CSS than stage IV patients [42,43].…”
Section: The Role Of Adjuvant Therapy Following Lymph Node Dissectionmentioning
confidence: 99%